Strategies in translating parallelism from english into Arabic in novel ' Moby Dick' - Anuar, Mohd Nor Ikbal (2015)
This study examines strategies in translating parallelism and factors in retaining parallelism in the Arabic translation of the novel of ‘Moby Dick’. Parallelism is a rhetorical device which stands for identical and equivalent constructions based on syntactic, phonological, morphological and numerical aspects. Translating parallelism is a challenging task for translators as languages differ at the syntactical, morphological and phonological levels. The present study aims at identifying parallelism in ‘Moby Dick’ and discussing the factors in retaining parallelism in ‘Moby Dick’. The study is guided by Chesterman’s (1997) syntactic strategy model and a contrastive analysis (CA) is also performed. The qualitative analysis is carried out by comparing ST and TT to identify the strategies employed by the translator and examining the factors in retaining parallelism in the TT. An in-depth analysis shows that based on Chesterman’s (1997) model, the translator used three strategies, namely literal translation, clause structure change and transposition. The researcher also found other translation strategies followed by the translator which are addition, omission, rhyme, lexical repetition and pattern repetition. Besides, the researcher discovered three factors in retaining parallelism which are a syntactic factor, paraphrase and communicative translation. The findings revealed that most parallelism occurred at the syntactical level and that the strategy most used by the translator was literal translation. The findings suggest that syntactic differences may not allow the translator to use any strategy to retain parallelism in the TT.